PENINGKATAN HASIL BELAJAR MAHASISWA MELALUI PENERAPAN MODEL DISCOVERY LEARNING DALAM MATA KULIAH KURIKULUM DAN PEMBELAJARAN DI PRODI PGSD FKIP UNIVERSTAS BENGKULU - Kustianti, Sri Ken; Agusdianita, Neza Agusdianita; Yuliantini, Nani (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2020)
The purpose of this study is to determine the increase in student learning outcomes by applying the discovery learning model to the curriculum and learning courses semester IB PGSD Study Program, Faculty of Education, University of Bengkulu. The method used is qualitative, classroom action research. The subjects of this study were 29 students of Elementary School Teacher Study Program. This study used test to measure student learning outcomes. Data from the test results were analyzed by qualitative descriptive. The results showed that there was an increase in the average test score of student learning outcomes from cycle I to cycle II, from 81 to 86. Completeness also increased from 76% in the first cycle to 85% in the second cycle.